Differentiation Versus Low Cost or Differentiation and Low Cost: A Contingency Framework - Hill, Charles W. L. (Academy of Management Review, 1988)
In the policy literature there is an assumption that the generic business-level strategies of differentiation and overall cost leadership are generally inconsistent. Contrary to this view, this article presents a contingency framework in which differentiation can be a means for firms to establish an overall low-cost position and discusses that a combination of differentiation and low cost may be necessary for firms to establish a sustainable competitive advantage.